2020
DOI: 10.1111/fog.12522
|View full text |Cite
|
Sign up to set email alerts
|

Nephrops norvegicus in the Adriatic Sea: Connectivity modeling, essential fish habitats, and management area network

Abstract: Knowledge of connectivity among subpopulations is fundamental in the identification of the appropriate geographical scales for stock status evaluation and management, the identification of areas with greater retention rates, and space‐based fisheries management. Here, an integration of hydrodynamic, biological, and habitat models results is used to assess connectivity and support the definition of essential fish habitats (EFH) in the Adriatic Sea, with reference to Nephrops norvegicus, an important benthic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Furthermore, the presence of muddy bottoms and other exogenous factors make it an ideal habitat for Norway Lobster, Nephrops norvegicus (Linnaeus, 1758) [67]. Numerous studies reported that here the population of Norway Lobster is characterised by high densities of individuals smaller, and growing slower, than those from other areas of the Adriatic Sea [68][69][70][71][72]. Among the other crustacean species occurring in the area, a commercial and ecological relevance is attributable to the Pink Shrimp, Parapenaeus longirostris (Lucas, 1846), which in the last decade showed a relevant abundance increase in the Mediterranean Sea [73,74].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of muddy bottoms and other exogenous factors make it an ideal habitat for Norway Lobster, Nephrops norvegicus (Linnaeus, 1758) [67]. Numerous studies reported that here the population of Norway Lobster is characterised by high densities of individuals smaller, and growing slower, than those from other areas of the Adriatic Sea [68][69][70][71][72]. Among the other crustacean species occurring in the area, a commercial and ecological relevance is attributable to the Pink Shrimp, Parapenaeus longirostris (Lucas, 1846), which in the last decade showed a relevant abundance increase in the Mediterranean Sea [73,74].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used biophysical larval transport models to estimate N . norvegicus larval dispersal (Marta‐Almeida et al, 2008; McGeady et al, 2021; Melaku Canu et al, 2020; O'Sullivan et al, 2015; Phelps et al, 2015). However, none have simulated larval transport on multiple mud grounds over a long time series (>10 years) to determine the extent of interannual variability in larval dispersal and population connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Here we focused on the deep water rose shrimp that is managed as a straddling stock, due to poor information on its spatial structure. Gaining information on the stocks structure and on the connectivity between population units is thus essential to solve the mismatch between biological and management units and identify the appropriate geographical scales for stock assessment and management (e.g., Cadrin, 2020; Fiorentino et al, 2014; Hidalgo et al, 2019; Melaku Canu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions of Lagrangian particles with the coastal boundary, could affect the dynamics of dispersal. In our simulations, similarly to what is generally done in larval dispersal studies (e.g., Melaku Canu et al, 2020; Palatella et al, 2014), we did not consider larval beaching/stranding on the coast but we applied reflective boundary conditions that, depending on the geometry of the domain, the run length and the strength of the velocity field, could affect the GTCs and the hotspot regions. Many models based on Lagrangian computations, analyzed the stranding effect, showing that the stranding probability of particles may be meaningful, especially in conjunction with the particle resuspension probability (see Hinata et al, 2020; Liubartseva et al, 2018; Onink et al, 2021 for applications to marine plastic debris), and the vertical migration (see Berline et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation